PENGARUH PERUBAHAN KASUS POSITIF COVID-19 DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM DI INDONESIA - Santi Fitriani; Ahmad Setiawan Nuraya (Universitas Multimedia Nusantara, 2022)
Abstract- This study aims to analyze whether the Jakarta Composite Index is affected by changes in the positive cases of Covid-19 in Indonesia and the Rupiah against the US. This research was motivated by the high number of positive cases of COVID-19 in Indonesia which affected economic activity in Indonesia. The sample in this study was determined using the purposive sampling method, so that a sample of 52 observations was obtained. The variables in this study were the weekly average data of the Composite Stock Index (IHSG) on the Indonesia Stock Exchange and Positive Cases of Covid-19 and the Rupiah against US which is for the period March 2, 2020 – March 7, 2021. This study uses secondary data in the form of time series measured using the multiple linear regression analysis method. The results of the study found that the Positive Case of Covid-19 had a significant negative effect on the JCI and the Rupiah on the US had a non-significant positive effect. Keywords: Composite Stock Price Index; COVID-19; US; Share; Capital market